Strategic learning alliances and cooperation: A game theory perspective on organizational collaboration - Issam Tlemsani; Robin Matthews; Mohamed Ashmel Mohamed Hashim (Economies, 2024)
This study explores the dynamics of international strategic learning alliances through the lens of game theory, incorporating complexity and cooperative game theories to develop a model of organizational evolution. Using simulations and network resources, we examine 1200 cases to assess the costs and benefits of inter-organizational cooperation, with a focus on mutual payoffs and strategic decision-making. Our research addresses key gaps in the literature by analyzing how game-theoretic structures impact the success of alliances, providing actionable insights for firms aiming to enhance strategic partnerships. The findings offer valuable guidance for international partners involved in learning alliances, emphasizing the importance of aligning institutional responses with perceived risks and opportunities. By identifying the motivations and success factors behind strategic alliances, organizations can better formulate optimal strategies for collaboration. This paper contributes to the discourse on inter-firm cooperation by highlighting the complexities of strategic learning alliances and offering new perspectives for future research.
Keywords: 330; strategic decision-making; strategic learning alliances; collaboration games; inter-organizational cooperation; game theory; simulation models; payoffs